Beta2-Agonists and Asthma in Children - Guy Lapierre (Canadian Respiratory Journal)
Due to the growing prevalence and morbidity of asthma in children in the past few years, Canadian physicians have addressed several issues concerning the correct use of beta2-agonists for the treatment of asthma. These issues include the optimum delivery systems for beta2-agonists, their appropriate dosages in children, infants and toddlers, and whether tachyphylaxis occurs with their chronic use.